JMUAS 2019
DOI: 10.36602/jmuas.2019.v01.01.15
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reusing treated wastewater in irrigation on some chemical soil properties and wheat crop growth

Abstract: This study was aimed to investigate the suitability of reusing of treated wastewater to irrigate wheat crop and its impact on soil properties. The study was conducted during the Agricultural season 2014-2015, at Sirte, Libya. The climate of this area characterized by dry and hot in summer, cool and rained in winter, as well as the annual rainfall in the range of 175 mm to 200 mm, so the area is considered as semi-arid area. The experiment was designed to use treated wastewater under different managements ((W1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effluents of wastewater treatment plants usually contain organic chemicals. Such chemicals remaining in the water after the treatment process may cause hazards to human health [11]. Microbiological studies are considered as a source of information to avoid health risks.…”
Section: Health Risks Of Agricultural Wastewatermentioning
confidence: 99%
“…The effluents of wastewater treatment plants usually contain organic chemicals. Such chemicals remaining in the water after the treatment process may cause hazards to human health [11]. Microbiological studies are considered as a source of information to avoid health risks.…”
Section: Health Risks Of Agricultural Wastewatermentioning
confidence: 99%
“…These benefits were mainly non‐use benefits related to the aesthetic enjoyment of clean water in the reclaimed stretch of coast where the sewage discharge may not return or occur in a way that significantly reduces seawater pollution. Milad et al (2019) confirmed that the reuse of treated wastewater leads to water savings, expansion of cultivated areas for crop production and reduced costs related to chemical fertilizers. The Food and Agriculture Organization of the United Nations (2016) assessed treated wastewater intended for agriculture in Lebanon.…”
Section: Introductionmentioning
confidence: 99%